Tamiḻpperu vaḷḷal - Aruṇācalam Piḷḷai, Mu., 1903-1973 (SAMP early 20th-century Indian books project, 1953)
Biography of Raja Sir Annamalai Chettiar, 1881-1948, educationist, administrator, and philanthropist from Tamil Nadu.